Evaluation of oral and topical herbal formulations used in Unani medicine for treatment of psoriasis and its effect on inflammatory biomarkers – a randomized controlled clinical trial - Rahi, Tariq; Islam, Naqueeb Ul; Pandith, Riyaz Ahmed; Akbar, Seema; Rafeeqi, Towseef Amin (European journal of integrative medicine, 2022)
Unani medicine, one of the complementary and alternative medicines which has mentioned the treatment options for Psoriasis, a chronic skin disease. The aim of the study was to evaluate the safety and efficacy of Unani herbal formulations in patients with psoriasis on systemic scientific parameters. This parallel group, randomized, single blind clinical trial compared Unani herbal formulations comprising of both an oral and a topical preparation with Betamethasone Valerate cream as a control. The total number of patients completing the trial was 26 in each group and treatment was given for 90 days with clinical follow-up after every 15 days. The Psoriasis Area and Severity Index (PASI) score and the inflammatory biomarkers were evaluated at the baseline and at the end of the study. There were no significant differences in general clinical characteristics (P>0.05) of test and control groups and evidentally, the 95% CIs of two groups overlap for PASI score at baseline and at the end of treatment. There was improvement in the dominant features of psoriasis with decrease in PASI of patients from the baseline to the end of study in both groups. No adverse effects were observed and all the blood safety parameters remained within the normal range. The ESR and TNF-α values were found higher in psoriatic patients and there was reduction in TNF-α values in test group (P= 0.08) with less reduction in control group (P=0.10). The tests suggests that Unani herbal formulations can be safely and effectively used in the patients with psoriasis.